METHODOLOGICAL PROBLEMS OF PRACTICAL RADIOGENIC RISK ESTIMATIONS - A. Т. Gubin; V. A. Sakovich (Радиационная гигиена, 2015)
Mathematical ratios were established according to the description of the calculation procedure for the values of the nominal risk coefficient given in the ICRP Recommendations 2007. It is shown that the lifetime radiogenic risk is a linear functional from the distribution of the dose in time with a multiplier descending with age. As a consequence, application of the nominal risk coefficient in the risk calculations is justified in the case when prolonged exposure is practically evenly distributed in time, and gives a significant deviation at a single exposure. When using the additive model of radiogenic risk proposed in the UNSCEAR Report 2006 for solid cancers, this factor is almost linearly decreasing with the age, which is convenient for its practical application.